2015
DOI: 10.1109/tvcg.2014.2330617
|View full text |Cite
|
Sign up to set email alerts
|

Perception-Based Evaluation of Projection Methods for Multidimensional Data Visualization

Abstract: Abstract-Similarity-based layouts generated by multidimensional projections or other dimension reduction techniques are commonly used to visualize high-dimensional data. Many projection techniques have been recently proposed addressing different objectives and application domains. Nonetheless, very little is known about the effectiveness of the generated layouts from a user's perspective, how distinct layouts from the same data compare regarding the typical visualization tasks they support, or how domain-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…The similarity between patterns can be measured by relative ranking using some Likert scale [TBB*10] or by manual grouping of similar scatterplot based on their thumbnail images [DBH14, PKF*16]. Cluster patterns can also be characterized by identifying their elements using a lasso selection, or the overall pattern evaluated by counting the number of clusters [EMdSP*15].…”
Section: Experiments 1: Gathering Data For Modelingmentioning
confidence: 99%
“…The similarity between patterns can be measured by relative ranking using some Likert scale [TBB*10] or by manual grouping of similar scatterplot based on their thumbnail images [DBH14, PKF*16]. Cluster patterns can also be characterized by identifying their elements using a lasso selection, or the overall pattern evaluated by counting the number of clusters [EMdSP*15].…”
Section: Experiments 1: Gathering Data For Modelingmentioning
confidence: 99%
“…Employing dimensionality reduction techniques [11], [13], [14] is a common approach to deal with many similarities at once. Typically, the results of dimensionality reduction are visualized as 2D scatterplots, in which the distances between points merely approximate the real distances.…”
Section: Related Workmentioning
confidence: 99%
“…Typically, the results of dimensionality reduction are visualized as 2D scatterplots, in which the distances between points merely approximate the real distances. Controlled user studies have shown that users find it difficult to understand the placement of the points and how accurately the real distances have been preserved [9], and that there is a dependency between task and projection performance [13]. Users must also develop trust in the projection and representation to use the visualization confidently [10].…”
Section: Related Workmentioning
confidence: 99%
“…Etemadpour et al [23] proposed perception-based evaluation of projection methods based on empirical data but not perceptual models and quality metrics as in our approach. Color optimization in scatterplots was adopted by Chen et al [24] to improve the discernibility of multiple classes when the scatterplot is overplotted.…”
Section: Automatic and Semi-automatic Designmentioning
confidence: 99%